Caixa ecológico: modelo implementado em um supermercado de Curitiba, Paraná, Brasil - Albach, Dulce de Meira (2007)
This project established an effective waste management action concerning the packages, which, nowadays, significantly add to the urban solid waste. Aiming the minimization of the environmental impacts caused by its indiscriminate discard, the model was characterized by the installation of a distinct check-out in a supermarket of Curitiba. The consumers were able to make the anticipated discard of the plastic and/or paper packages and consequently send it correctly for the recycling process. The money collected from the packages’ selling to recycling companies was donated to a charity institution, stimulating therefore consumers’ participation. The consumers had been stimulated as well to bring their own bag for the transport of the acquired products, aiming the reduction of the amount of wasted plastic bags. The acceptance of the model was evaluated by means of a quantitative inquiry, when 350 consumers who had registered their purchases at the Ecological Check-out were interviewed in the period of October 10 to 31, 2006. The results showed that 100% of the consumers would contribute to the Ecological Check-out again; 83% would give preference to the supermarket for this initiative; 45% had discarded up to 7 packages and 3% had brought their own bag. A qualitative survey, performed with the involved Ecological Check-out operators, demonstrated however that the practical attitudes do not correspond to the theoretical affirmations and many consumers who had alleged to support the idea, did not accomplish the action. Improvements in the supermarket’s waste management were also been stimulated by the project: Trash cans for selective collection of internal and external residues were installed and the volume collected was added to that collected by the Ecological Check-out. This project attempted to effectively alert the consumers for the value of their participation in the minimization of residues’ amount, mainly the packages, which are potential contributors to the current environmental picture. It was observed, however, that the difficulty lies in the change of habits, mainly of the consumers, and that information programs are required.